Biological activities and phytochemical screening of Elaeodendron croceum (Thunb.) DC. Leaves and Stem barks Extracts - Samuel Wale Odeyemi; Anthony Jide Afolayan (International Journal of Phytomedicine, 2017)
Background: From reports Elaeodendron croceum has been used traditionally for spiritual cleansing, anti-obesity, anti-inflammatory and for the management of diabetes. The leaves and bark extracts were therefore analyzed for its biological activities. Materials and methods: The antibacterial activities of E. croceum leaves and stem barks were evaluated against both Gram positive and gram negative bacteria using agar well diffusion method. The analysis for the phytochemical contents, antioxidant and anti-inflammatory activities of the leaves and barks were determined using standard procedures. Results: The S. aureus, S. flexneri, E. faecalis and S. typhimurium were susceptible to the aqueous leaves and stem barks extracts of Elaeodendron croceum while S. aureus was susceptible to only the aqueous leaf extract. The antibacterial activity showed MIC ranging from 0.625 – 2.5 mg/ml. The composition of flavonoids (52.72 mg/g), proanthocyanidins (32.66 mg/g), alkaloids (65.44 mg/g) and saponins (68.21 mg/g) were significantly higher in the aqueous leaf extract while phenols (94.13 mg/g) content was higher in the aqueous bark extract. The free radical scavenging activity using ABTS, FRAP and DPPH showed that the extracts possess good free radical scavenging activities with different free radical species that is comparable with ascorbic acid and also showed significant inhibitory activity on protein denaturation as an indication of anti-inflammatory potential. Conclusion: These findings support the folkloric usage of Elaeodendron croceum and indicates that it can be used to manage diseases caused by the tested organisms. The presence of alkaloids, flavonoids, total phenols and proanthocyanidins, previously suggested to have antioxidant, anti-inflammatory and antibacterial activity indicate that E. croceum is a potential source of anti-inflammatory, free radical scavenging and antimicrobial agents.